Domestic work as a job opportunity for economically deprived women: Causes and consequences of being a maidservant - Tayyaba Rafique Makhdoom; Muhammad Nawaz Baloch; Azeem Akhtar Bhatti (International Journal on Women Empowerment, 2020)
Background: Domestic workers comprise a significant part of the national workforce and serve as the backbone for various families in our society. This community still lives below the poverty line and striving for a better life. This study investigated the factors responsible for women to become domestic workers and identified their problems. Domestic maids' literature is scant, especially in Pakistan; negligible work is done on the topic, which is an impetus to contribute. It will help in devising some policies for the wellbeing of this economically deprived segment of society. Methodology: This study explores maids' data about demographics, employment, problems and their access to welfare programs. Semi-structured interviews — comprised of closed-ended and open-ended questions — were conducted from 14 domestic maids working in Hyderabad and Jamshoro districts, selected through a convenient sampling technique. The data were analyzed with frequency and crosstabs and thematic analysis. Results: Old age, extended work experience, lack of education, being married, number of dependents and low income were found the common factor in this occupation. Irresponsible male members, absence of male members, insufficient family income, an accusation of theft, deteriorating health, being overburdened, and non-access to welfare programs were found to be the main problems for housemaids. Conclusion: The elimination of this occupation is not recommended, as they play a very vital role in our society, but a change in attitude and conduct while dealing with maids is suggested. Whereas, there is a need for agencies, which can provide a pool of labour as domestic servants, as both employer and employee rights can be protected.